2. Effect of the Addition of Palm Kernel and Ammoniated Lemongrass Waste (Cymbopogon Nardus) on the Quality of Fresh Semen of Thin Tailed Sheep as a Partial Replacement of Basal Feed - Fitrah Khairi; Cut Islami Dini; Cut Intan Novita; Siti Rani Ayuti (Jurnal Medika Veterinaria, 2021)
In this study, three sheep aged two years old with a bodyweight of 20-25 kg were used. The treatments consisted of R1 (10% palm kernel cake and ammoniated citronella waste), R2 (20% oil palm kernel cake and ammoniated citronella waste) and R3 (30% oil palm kernel cake and ammoniated citronella waste). Research design used was Latin Square Design with three treatments and three replications. The parameters of semen observed were macroscopic and microscopic quality which included color, odor, volume, consistency, pH, concentration, mass movement and individual motility. The results showed that the administration of palm kernel cake with concentrations of 10%, 20%, and 30% and ammoniated citronella waste had no significant effect (P0.05) on the quality of fresh thin-tailed sheep's semen both macroscopically and microscopically. The semen had an average volume of 0.62 ml, creamy in color, had a characteristic as semen odor, thick in consistency and has a normal pH of 6.89. Microscopically, it had average concentration of 1809x106/ml, average mass movement of ++, and  average individual motility of 57.57%. Based on the results, the administration of palm kernel cake and ammoniated citronella waste does not affect the quality of the fresh semen of thin-tailed sheep, both macroscopically and microscopically.